Mock representations of horror in television dramas (Al-Academy, 2026)
Horror series are an important genre in the world of television drama, possessing the ability to manipulate viewers' emotions by evoking fear and anticipation through visual elements These shows commonly utilize shared elements to provoke fear and suspense, such as characters facing obstacles, the use of location and lighting to create a psychologically thrilling atmosphere With the technological and artistic advancements in the Arab world, production companies have started creating horror works, drawing inspiration from folklore, magic stories, and Arab literary works This research will explore the mechanisms used to handle such texts within a theoretical framework